Process Parameters and Tool Design in Friction Stir Extrusion: A Sustainable Recycling Technique - Akbari, Mostafa; Asadi, Parviz; Behnagh, Reza Abdi; Bedir, Fevzi; Choupani, Naghdali; Sadowski, Tomasz (Wiley, 2025)
Friction stir extrusion (FSE) is a versatile technique that plays a dual role in sustainable recycling and shaping of materials. This method involves a rotating mandrel and a fixed matrix within a mold, where compressed waste metal chips or primary bulk materials are introduced. The rotating mandrel exerts continuous axial pressure, generating frictional heat that softens and bonds the materials together. As the mandrel advances, the materials are reshaped and extruded through the cavity inside the mandrel or the space between the mandrel and the matrix, resulting in the desired product, such as wires or pipes. FSE finds applications in recycling machining wastes, improving powder metallurgy products, producing wire raw materials, creating structures with fine microstructures, and developing new alloys and composites. The resulting materials exhibit refined grains, leading to enhanced mechanical and metallurgical properties. This review article compiles experimental studies exploring the mechanical and microstructural characteristics of samples manufactured using FSE for recycling, reshaping, alloying, or bilayer production. Additionally, it discusses various tool, mold, and machine designs proposed by researchers. Beyond its unique properties, FSE is highlighted as an energy-efficient, sustainable, and eco-friendly process.
Keywords: friction stir extrusion; material flow; microstructure; recycling; sustainability; tool design